Strength and toughness improvement mechanism research method for water-excited cold-mixed asphalt mixture
By comprehensively using a variety of test and analysis methods, the mechanical behavior and toughness enhancement mechanism of water-activated cold-mixed asphalt mixture was analyzed, and the problem of single strength and toughness evaluation methods of the existing technology inter-cold-mixed asphalt mixture was solved, achieving strong toughness improvement and road quality improvement.
Patent Information
- Application Number
- CN202510080344.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-17
- Publication Date
- 2025-04-29
AI Technical Summary
In the prior art, the strength and toughness evaluation method of cold-mixed asphalt mixture is single, relies too much on traditional mechanical indicators, and does not fully consider the physical and chemical effects between the diluent, curing agent and asphalt, making it difficult to reveal the strength and toughness enhancement mechanism of cold-mixed asphalt mixture.
By comprehensively using a variety of test and analysis methods, including dynamic shear rheology test, bending beam creep stiffness test, fluorescence microscopy test, infrared spectroscopy analysis, nanoindentation test, uniaxial penetration test and semicircular bending test, the mechanical behavior evolution law and strength and toughness lifting mechanism of water-excited cold-mixed asphalt mixture are systematically analyzed.
It effectively improves the strength and toughness of water-activated cold-mixed asphalt mixture, reduces cracking of cold-mixed asphalt pavement, improves the quality of pavement construction, and extends the service life of the pavement.
Smart Images

Figure BSA0000299950920000041 
Figure BSA0000299950920000042 
Figure BSA0000299950920000043
Abstract
Description
Technical Field
[0001] The present application provides a method for studying the mechanism of improving the strength and toughness of a water-activated cold-mix asphalt mixture, and belongs to the technical field of asphalt mixture performance enhancement. Background Art
[0002] As the country attaches great importance to green transportation and ecological environment protection, it is necessary to develop low-energy and low-pollution road construction materials to meet the technical requirements of "green construction". Cold-mix asphalt mixture has become one of the research focuses due to its low energy consumption and low emissions. However, the strength formation process of cold-mix asphalt mixture takes a long time, and the initial strength is usually low. Construction at room temperature makes it difficult to effectively compact the mixture, resulting in low strength and poor durability. At present, the mechanical properties and road performance of cold-mix asphalt mixture have been improved through methods such as material modification and mixture design optimization.
[0003] Asphalt mixture is a granular composite material composed of asphalt, aggregate and pores. Its performance is affected by factors such as the proportion of each component, microstructure morphology, and interaction between components. Therefore, the study of the mechanical properties of asphalt mixture is also relatively complicated. The shear strength of asphalt mixture is determined by the properties of asphalt, the shear strength of the interface between aggregate and asphalt, and the embedding between aggregates. Reactive cold-mix asphalt mixture is generally obtained by cross-linking and curing polymer binder with solvent to obtain a high-molecular polymer binder. The strength is formed by the reactive diluted asphalt-inorganic active powder curing agent system, which solves the problem of insufficient strength of traditional cold-mix technology and significantly enhances the bonding force of asphalt and the mechanical properties of the mixture.
[0004] There are four main methods for studying the strength and toughness of asphalt mixtures: the first is to evaluate the strength and toughness of asphalt mixtures through conventional mechanical properties tests; the second is to use digital image processing technology, such as using X-rays, CT machines and other equipment to collect images of materials, and after processing, obtain information on the surface and internal structure of the materials, and finally use software to analyze the stress-strain state; the third is to use numerical simulation methods such as discrete elements and finite elements to simulate the interaction between aggregate particles and the stress-strain relationship of asphalt under different conditions through digital models to analyze the mechanical properties of asphalt mixtures, but the accuracy and applicability of the model still need to be verified and improved; the fourth is to use chemical and physical analysis to study the chemical structure changes of asphalt and additives through chemical analysis methods such as infrared spectroscopy analysis and thermogravimetric analysis, revealing the intrinsic connection between chemical structure and mechanical properties.
[0005] The strength and toughness of asphalt mixtures are affected by many factors, including material composition, external environmental conditions, loading methods, etc. The coupling mechanism between these factors is complex and the quantitative relationship is difficult to determine. Due to the presence of diluent components and curing agents in water-activated cold mix asphalt mixtures, the rheological properties of asphalt mortar will also be different from those of ordinary asphalt. However, the existing evaluation methods are too dependent on certain traditional mechanical indicators and do not fully consider the influence of asphalt mortar rheological properties. In addition, there are complex physical and chemical interactions between diluents, curing agents, asphalt and other components, such as adhesion between asphalt and aggregates, asphalt modification effects, cohesion between aggregates, volcanic ash effects of curing agents, and water excitation effects. In addition, the presence of curing agents will cause the mechanical properties of the mixture to change over time. At present, the evaluation methods for such mixtures have obvious limitations and fail to fully reveal these interactions and the dynamics of their curing process.
[0006] Therefore, this application will comprehensively use a variety of tests and analysis methods to conduct macroscopic and microscopic related tests on diluted asphalt and its mixture before and after adding water, and more comprehensively and accurately analyze the evolution law of the mechanical behavior of water-activated cold-mix asphalt mixture and the mechanism of improving strength and toughness from the aspects of macroscopic mechanical indicators, fracture absorption energy angle, microscopic morphology, chemical bond changes, etc., which will help to improve the quality of pavement construction, reduce early damage and later maintenance costs, and extend the service life of the pavement. Summary of the invention
[0007] (1) Technical issues
[0008] The purpose of this application is to provide a research method for the mechanism of improving the strength and toughness of water-activated cold-mix asphalt mixtures, so as to solve the problems of the current cold-mix asphalt mixture strength and toughness evaluation method being single, overly dependent on traditional mechanical indicators, not fully considering the physical and chemical effects between diluents, curing agents and asphalt, and difficulty in revealing the mechanism of improving the strength and toughness of cold-mix asphalt mixtures, thereby effectively improving the strength and toughness of water-activated cold-mix asphalt mixtures and reducing cracking of cold-mix asphalt pavements.
[0009] (2) Technical solution
[0010] In order to further study the mechanism of improving the strength and toughness of water-activated cold-mix asphalt mixtures, and to solve the problems of the current cold-mix asphalt mixture strength and toughness evaluation methods being single, overly dependent on traditional mechanical indicators, not fully considering the physical and chemical interactions between diluents, curing agents and asphalt, and difficulty in revealing the mechanism of improving the strength and toughness of cold-mix asphalt mixtures, this application first tests the high and low temperature mechanical properties of water-activated diluted asphalt after curing from the asphalt level, and uses a fluorescence microscope and an infrared spectrometer to observe the surface and chemical bond change information of water-activated diluted asphalt after curing; then, from the mixture level, the mechanical indicators of the mixture sample are obtained through a nanoindentation test, the mixture sample is subjected to a uniaxial penetration test, and then combined with the test results of the semicircular bending test, the principle of enhancing the shear resistance and fracture strength of the mixture after adding water is analyzed. The technical scheme of the present application is as follows: two kinds of water-activated diluted asphalts with and without water added and their cold-mix asphalt mixtures are selected to study the mechanism of improving strength and toughness, the asphalt samples are subjected to dynamic shear rheology test and bending beam creep stiffness test respectively to obtain the high and low temperature performance data of the asphalt, the dispersion of the reactants and the degree of reaction after the water-activated diluted asphalt is solidified are observed by fluorescence microscopy, and then the asphalt samples are subjected to Fourier infrared spectroscopy test to obtain the changes in the chemical bonds or functional groups of the asphalt before and after the addition of water; then, the mechanical indicators such as hardness, modulus, and viscoelastic parameters of the two mixtures are obtained by nanoindentation test, and the mixture samples are subjected to uniaxial penetration test and semicircular bending test to obtain the uniaxial penetration shear strength and the maximum load, fracture strength and fracture energy that can be sustained; finally, the mechanical parameters, fracture energy changes and microscopic morphology changes are comprehensively considered to further reveal the mechanism of improving strength and toughness of the water-activated cold-mix asphalt mixture.
[0011] (3) Beneficial effects
[0012] Asphalt itself is a mixture with extremely complex components, and it is difficult to study the microscopic modification mechanism; in addition, the interaction relationship between admixtures and asphalt is complex and diverse, not only physical and chemical effects, but also multiple effects coexist in most cases. The present application provides a method for studying the mechanism of improving the strength and toughness of water-activated cold-mix asphalt mixtures. The high and low temperature performance of water-activated diluted asphalt before and after curing, the dispersion degree of water reactants and chemical bond changes are collected by dynamic shear rheology test, bending beam creep stiffness test, fluorescence microscope test, and infrared spectroscopy analysis. Then, the changes in mechanical performance indicators of water-activated cold-mix asphalt mixtures before and after water is added are studied by nanoindentation test, uniaxial penetration test and semicircular bending test. The mechanism of improving the strength and toughness of water-activated cold-mix asphalt mixtures is systematically and comprehensively studied from multiple angles. This not only helps to systematically understand the mechanism of improving material performance from the molecular to the macroscopic level, but also provides a scientific basis for optimizing mixture design, improving the quality and service life of pavement engineering, and has important theoretical and practical significance. DETAILED DESCRIPTION
[0013] This application provides a research method for improving the toughness of water-activated cold-mix asphalt mixture, and the specific implementation steps are as follows:
[0014] (1) SBS modified asphalt and water-cured water-activated diluted asphalt were selected as samples. The high-temperature performance of SBS modified asphalt and water-activated diluted asphalt after curing was tested by dynamic shear rheometer. The test temperatures were 46°C, 52°C, 58°C, 64°C, 70°C, 76°C and 82°C, respectively. Continuous sinusoidal alternating load was applied. The strain control method was used to measure the complex modulus G* and phase angle δ of the two asphalt samples. The rutting factor G* / sinδ was calculated to evaluate the high-temperature performance of the two asphalts.
[0015] (2) The low-temperature crack resistance test of SBS modified asphalt and cured water-activated diluted asphalt was carried out using a bending beam rheometer. At -12°C and -18°C, constant stress was applied and the loading lasted for 240 seconds. During the test, the stiffness modulus and creep rate at 8 seconds, 15 seconds, 3 seconds, 60 seconds, 120 seconds and 240 seconds were recorded. The low-temperature crack resistance of the two asphalt samples was evaluated using the measured creep stiffness modulus and creep rate.
[0016] (3) Conducting a fluorescence microscope test on the water-excited diluted asphalt after curing, using a stereo fluorescence microscope to observe the microstructure of the curing agent and its hydration reaction products in the asphalt, using a green fluorescent protein observation mode with a magnification of 150 times, and using a fluorescence microscope to observe the dispersion uniformity and reaction degree of the hydration reaction products in the water-excited diluted asphalt after water curing;
[0017] (4) Fourier transform infrared spectroscopy test was carried out on the water-excited diluted asphalt before and after water curing. The test was carried out in mid-infrared-reflection mode. The resolution of the Fourier transform infrared spectroscopy test was 4 cm -1 , the scanning times were 32 times, and the wave number scanning range was 400~4000cm -1 , using Fourier transform infrared spectroscopy to study the changes in chemical bonds or functional groups in water-induced diluted asphalt before and after water curing;
[0018] (5) Water-activated diluted asphalt, optimal oil-to-stone ratio and AC-13F median asphalt mixture gradation were used to prepare water-activated cold mix asphalt mixture. Cube mixture specimens with a side length of 20 mm were made under water and no water conditions for nanoindentation test. The maximum load and loading and unloading rates were set to 0.1 mN and 0.01 mN / s respectively, and the creep full load time was set to 100 s. The hardness, modulus, viscoelasticity and toughness parameters of the two mixture specimens with and without water were obtained.
[0019] (6) According to the "Test Procedures for Asphalt and Asphalt Mixtures for Highway Engineering" (JTG E20-2011), cylindrical specimens with a diameter of 100 mm and a height of 100 mm of water-induced cold-mix asphalt mixture were prepared with and without water added. Uniaxial penetration tests were carried out using a universal material testing machine. The specimens were loaded uniformly at a loading rate of 1 mm / min until failure. The peak load was read and the cross-sectional area of the penetration rod was recorded. The uniaxial penetration shear strength τ of the two mixture specimens with and without water added was calculated using formula ①. s , where P is the peak load and A is the cross-sectional area of the penetration rod;
[0020]
[0021] (7) According to the Standard Test Method for Determination of Fracture Energy of Asphalt Mixtures by Semicircular Bending Test (AASHTO TP124-2016), semicircular bending specimens with a diameter of 100 mm and a height of 50 mm were prepared for water-induced cold mix asphalt mixtures with and without water added. The semicircular bending test was carried out under the conditions of 15°C and -20°C using the stress control mode, four stress ratios of 0.2, 0.3, 0.4 and 0.5, the loading frequency of 10 Hz, the load waveform of half sine wave, and no rest time. The radius, thickness and incision length of the specimen were recorded, the peak load and average load line displacement when the specimen was completely broken were read, and the fracture strength σ of the two mixture specimens with and without water added at room temperature and low temperature were calculated using Formulas ②, ③, ④ and ⑤ respectively. m , fracture energy G f , where r is the specimen radius, t is the specimen thickness, a is the specimen cut length, P is the peak load when the specimen is completely broken, and u is the average load line displacement;
[0022]
[0023]
[0024] W f =∫Pd u ④
[0025] A lig =(ra)t ⑤
[0026] (8) The high-temperature stability, low-temperature crack resistance, dispersion degree of hydration reaction products and functional group changes before and after curing of diluted asphalt before and after water addition were comprehensively compared and analyzed, as well as the hardness, modulus, viscoelasticity, toughness, shear resistance, fracture strength and fracture energy of water-activated cold-mix asphalt mixture before and after water addition. The mechanism of improving the strength and toughness of water-activated cold-mix asphalt mixture was revealed.
Claims
1. A method for studying the mechanism of improving the strength and toughness of water-activated cold-mix asphalt mixture, characterized in that The specific steps of this method are as follows: (1) SBS modified asphalt and water-cured water-activated diluted asphalt were selected as samples. The high-temperature performance of SBS modified asphalt and water-activated diluted asphalt after curing was tested by dynamic shear rheometer. The test temperatures were 46°C, 52°C, 58°C, 64°C, 70°C, 76°C and 82°C, respectively. Continuous sinusoidal alternating load was applied. The strain control method was used to measure the complex modulus G* and phase angle δ of the two asphalt samples. The rutting factor G* / sinδ was calculated to evaluate the high-temperature performance of the two asphalts. (2) The low-temperature crack resistance test of SBS modified asphalt and cured water-activated diluted asphalt was carried out using a bending beam rheometer. At -12°C and -18°C, constant stress was applied and the loading lasted for 240 seconds. During the test, the stiffness modulus and creep rate at 8 seconds, 15 seconds, 3 seconds, 60 seconds, 120 seconds and 240 seconds were recorded. The low-temperature crack resistance of the two asphalt samples was evaluated using the measured creep stiffness modulus and creep rate. (3) Conducting a fluorescence microscope test on the water-excited diluted asphalt after curing, using a stereo fluorescence microscope to observe the microstructure of the curing agent and its hydration reaction products in the asphalt, using a green fluorescent protein observation mode with a magnification of 150 times, and using a fluorescence microscope to observe the dispersion uniformity and reaction degree of the hydration reaction products in the water-excited diluted asphalt after water curing; (4) Fourier transform infrared spectroscopy test was carried out on the water-excited diluted asphalt before and after water curing. The test was carried out in mid-infrared-reflection mode. The resolution of the Fourier transform infrared spectroscopy test was 4 cm -1 , the scanning times were 32 times, and the wave number scanning range was 400~4000cm -1 , using Fourier transform infrared spectroscopy to study the changes in chemical bonds or functional groups in water-induced diluted asphalt before and after water curing; (5) Water-activated diluted asphalt, optimal oil-to-stone ratio and AC-13F median asphalt mixture gradation were used to prepare water-activated cold mix asphalt mixture. Cube mixture specimens with a side length of 20 mm were made under water and no water conditions for nanoindentation test. The maximum load and loading and unloading rates were set to 0.1 mN and 0.01 mN / s respectively, and the creep full load time was set to 100 s. The hardness, modulus, viscoelasticity and toughness parameters of the two mixture specimens with and without water were obtained. (6) According to the "Test Procedures for Asphalt and Asphalt Mixtures for Highway Engineering" (JTG E20-2011), cylindrical specimens with a diameter of 100 mm and a height of 100 mm of water-induced cold-mix asphalt mixture were prepared with and without water added. Uniaxial penetration tests were carried out using a universal material testing machine. The specimens were loaded uniformly at a loading rate of 1 mm / min until failure. The peak load was read and the cross-sectional area of the penetration rod was recorded. The uniaxial penetration shear strength τ of the two mixture specimens with and without water added was calculated using formula ①. s , where P is the peak load and A is the cross-sectional area of the penetration rod; (7) According to the Standard Test Method for Determination of Fracture Energy of Asphalt Mixtures by Semicircular Bend Test (AASH TOTP 124-2016), semicircular bend specimens with a diameter of 100 mm and a height of 50 mm were prepared for water-induced cold mix asphalt mixtures with and without water added. The semicircular bend test was carried out under the conditions of 15°C and -20°C using the stress control mode, four stress ratios of 0.2, 0.3, 0.4 and 0.5, the loading frequency of 10 Hz, the load waveform of half sine wave, and no rest time. The specimen radius, thickness and incision length were recorded, the peak load and average load line displacement when the specimen was completely broken were read, and the fracture strength σ of the two mixture specimens with and without water added at room temperature and low temperature were calculated using Formulas ②, ③, ④ and ⑤ respectively. m , fracture energy G f , where r is the specimen radius, t is the specimen thickness, a is the specimen cut length, P is the peak load when the specimen is completely broken, and u is the average load line displacement; IN f =∫Pd u ④ A lig =(r-a)t ⑤ (8) The high-temperature stability, low-temperature crack resistance, dispersion degree of hydration reaction products and functional group changes before and after curing of diluted asphalt before and after water addition were comprehensively compared and analyzed, as well as the hardness, modulus, viscoelasticity, toughness, shear resistance, fracture strength and fracture energy of water-activated cold-mix asphalt mixture before and after water addition. The mechanism of improving the strength and toughness of water-activated cold-mix asphalt mixture was revealed.